Museums of Byzantine History - Muazzamkhan Makhmudova Sultanmakhmudovna (Scientific Trends, 2024)
This article “Byzantine and Christian Museum”, “Byzantine Culture Museum”, “Byzantine Museum of the History of the Byzantine Empire” located on the Greek island of Zakynthos, “Byzantine Museum of Veria”, “Byzantine Museum of Antivouniotissa” in Corfu, “Byzantine Museum of the Holy Metropolis” in Paphos and provides information about the “Byzantine Museum” on the island of Rhodes.
Keywords: Greece, museum, pictogram, fresco, icon, island, reservoir.